Aplikasi Absensi dan Perhitungan Gaji Karyawan Menggunakan Metode Extreme Programming Berbasis Android (Studi Kasus Universitas Bung Karno) - Yovan Fiqri Alfauzan (CV. Shofanah Media Berkah, 2023)
The attendance process for Bung Karno University's employees that still using fingerprint machine is not effective and efficient because of the amount of the machine that only exists in one place so the employees have to queue to use that machine. Beside that, this fingerprint machine only records employees attendance each days, so when it is time to do absence data recapitulation, Personalia team has to manually calculate the total number of attendace for every employees each month, which that cause a delays in payment of employees salaries. The purpose of this research is to help solve the problem listed above with make an android based attendance and salary calculator application using Extreme Programming method. This employee attendance and payroll aplication uses Google Maps API that can capture the location of latitude and langitude data from the employee’s smartphone when performing on online absence. In addition, data in the form of dates and times in realtime is also recorded in one click of the absence button when doing an absence. The employees can also do other reporting related to permits or overtime work hour. That absence and reporting data can be stored and processed which next can be used as a reference in making the employee pay slips. With this application is expected to help the employee absence process and recapitulation of employee attendance and activity data so that the process of calculating employee salaries can be done appropriately and quickly.